Impact of bridge-to-bridge strategies from paracorporeal to implantable left ventricular assist devices on the pre-heart transplant outcome: A single-center analysis of 134 cases. Issue 4 (April 2021) - Nakajima Doi, Seiko; Seguchi, Osamu; Yamamoto, Masahiro; Fujita, Tomoyuki; Fukushima, Satsuki; Mochizuki, Hiroki; Iwasaki, Keiichiro; Kimura, Yuki; Toda, Koichi; Kumai, Yuto; Kuroda, Kensuke; Watanabe, Takuya; et al.
Highlights: We reviewed outcomes in patients with left ventricular assist devices (LVAD). Patients underwent bridge to bridge (BTB) strategy or primary implantable LVAD (iLVAD). Overall survival was not different between the BTB and iLVAD groups. BTB group had lower 1-year survival and freedom from the composite events rates. BTB strategy and preoperative bilirubin were independent predictors of 1-year outcome. Abstract: Background: In Japan, patients with heart failure who have a paracorporeal left ventricular assist device (pLVAD) and cannot be weaned from the VAD may undergo conversion to implantable continuous-flow LVAD ( iLVAD) via a bridge-to-bridge (BTB) strategy for bridge-to-transplantation (BTT). This study aimed to evaluate the real-world clinical status of BTB strategies. Methods: Among 134 patients who underwent iLVAD implantation for BTT, 34 patients underwent conversion from pLVAD to iLVAD (BTB group) and 100 patients underwent iLVAD implantation primarily (primary iLVAD group). The clinical characteristics and outcomes were compared between the two groups. Results: No significant difference was found in the overall survival between the two groups ( p  = 0.26; log-rank test). However, the 1-year survival rate and the 1-year freedom from the composite events of death, stroke, systemic infection, and bleeding rate were lower in the BTB group than in the primary iLVAD group (survival rate, 88.2% vs. 99.0%, p  = 0.0040; composite event-free survival rate, 26.1% vs. 49.8%, p  = 0.030; log-rank test). Multivariate analysis indicated that the BTB strategy [hazard ratio (HR) 1.70, 95% confidence intervals (CI) 1.03–2.72; p =0.036] and serum total bilirubin levels at iLVAD implantation [HR 1.31, 95% CI 1.00–1.65; p =0.043] were independent predictors of 1-year composite events. Conclusions: The BTB strategy is useful in providing long-term survival in patients with acute critical diseases. However, the early mortality rate after conversion is higher in patients who underwent the BTB strategy.